ormação continuada de professores: pressupostos teóricos para o ensino de matemática numa perspectiva freiriana - Morais, Daniela Pereira de (2025)
This study investigates the contribution of continuing teacher education, through pedagogical meetings, with teachers who work in the mathematics component in the final years of elementary education. This study is justified by the importance of making mathematics teaching more relevant to students, promoting a contextualized teaching process. Thus, the research question is defined as: in what ways can the implementation of a continuing education training guide for mathematics teachers, based on the Freirean framework, contribute to the teaching of this subject in the final years of elementary education? The general objective is to analyze the pedagogical effects of a didactic intervention, in the form of a proposal for continuing teacher education meetings, focusing on reflection on the teaching of Mathematics and the development of teaching planning from a critical perspective. As theoretical foundations, Paulo Freire and Ubiratan D’Ambrósio are adopted. As an Educational Product, a pedagogical meeting guide is presented, structured according to the Three Pedagogical Moments (3PM), with proposals for studies, reflections, and teaching planning, developed from the Freirean framework. The research adopted a qualitative methodology, of the action research type, and used participant observation, questionnaires, and records produced by teachers as instruments. Based on Content Analysis, three categories were established: dialogicity as a condition for problem-posing learning; collectivity as a necessary strategy for transforming and qualifying the teaching process; and reality as the starting point of a transformative teaching process. The final results show that the guide enhances pedagogical practice by promoting dialogicity and collectivity, consolidating itself as an efficient strategy for transforming mathematics teaching from a more critical and meaningful perspective. It is concluded that continuing education, constructed and developed together with the collective of teachers, mobilizes reflection and transformation of teaching based on the specific situations of the school context. It was also observed that the teaching methodology grounded in the Three Pedagogical Moments brought the teaching process closer to teachers’ experiences, being based on constant dialogue and demonstrating the crucial importance of understanding students’ life contexts. The Educational Product linked to this dissertation is free, open-access, and available for download on the EduCapes Portal (http://educapes.capes.gov.br/handle/capes/1174425) and on the PPGECM-UPF website (https://www.upf.br/ppgecm/dissertacoes-e-teses/dissertacoes).